Antara Warisan dan Reformasi: Menyikap Konsep Islam Sinkretis dan Islam Murni dalam Masyarakat Muslim - Ulul Aedi (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
The society’s response to the process of Islamization in Indonesia takes a variety of forms, some accept Islam kaffah, some are accepting Islam half-heartedly, some express rejection of Islam. The research aims to present two kinds of Islam that exist in Indonesia, namely, syncretic Islam and puritanical Islam. This research uses a literature study to understand the concepts of syncretic Islam and puritanical Islam. Syncretic Islam has a soft character by mixing it with local culture. Meanwhile, puritan Islam offers a hard character by affirming its rejection of all forms of mysticism in Islam. Syncretism is a concept that seeks to combine elements of two or more religions with cultural aspects.